[(eta 5-C5H5)Fe(CO)2]2B(2,4,6-Me3C6H2): synthesis, spectroscopic and structural characterization of a transition metal complex containing an unsupported bridging borylene ligand. - Aldridge, S; Coombs, D; Jones, C (2002)
The synthesis and characterisation of the dinuclear iron complex [(eta 5-C5H5)Fe(CO)2]2B(2,4,6-Me3C6H2) containing an unsupported bridging borylene ligand are reported.